Quetiapine induces myocardial necroptotic cell death through bidirectional regulation of cannabinoid receptors. (1st October 2019) - Li, Xiaoqing; Peng, Zhao; Zhou, Yiling; Wang, Jing; Lin, Xinyi; Dong, Xiaoru; Liu, Xiaochen; Jiang, Jieqing; Jiang, Yan; Li, Liliang
Highlights: Quetiapine remarkably induced necroptosis. CB1R antagonists or CB2R agonists inhibited necroptosis. CB1R antagonists or CB2R agonists protected against quetiapine cardiotoxicity. Abstract: Quetiapine is a common atypical antipsychotic used to treat mental disorders such as schizophrenia, bipolar disorder, and major depressive disorder. There has been increasing number of reports describing its cardiotoxicity. However, the molecular mechanisms underlying quetiapine-induced myocardial injury remain largely unknown. Herein, we reported a novel cell death type, quetiapine-induced necroptosis, which accounted for quetiapine cardiotoxicity in mice and proposed novel therapeutic strategies. Quetiapine-treated hearts showed inflammatory infiltration and evident fibrosis after 21-day continuous injection. The specific increases of protein levels of RIP3, MLKL and the phosphorylation of MLKL showed that quetiapine induced necroptotic cell death both in vivo and in vitro . Pharmacologic blockade of necroptosis using its specific inhibitor Necrostatin-1 attenuated quetiapine-induced myocardial injury in mice. In addition, quetiapine imbalanced the endocannabinoid system and caused opposing effects on two cannabinoid receptors (CB1R and CB2R). Specific antagonists of CB1R (AM 281, Rimonabant), but not its agonist ACEA significantly ameliorated the heart histopathology induced by chronic quetiapine exposure. By contrast, specific agonists of CB2R (JWH-133, AM 1241), but not its antagonist AM 630 exerted beneficial roles against quetiapine cardiotoxicity. The protective agents (AM 281, Rimonabant, AM 1241, and JWH-133) consistently inactivated the quetiapine-induced necroptosis signaling. Quetiapine bidirectionally regulates cannabinoid receptors and induces myocardial necroptosis, leading to cardiac toxic effects. Therefore, pharmacologic inhibition of CB1R or activation of CB2R represents promising therapeutic strategies against quetiapine-induced cardiotoxicity.